The Role of Cooperation in Increasing Farmers’ Welfare in Lampung Province - Dyah Aring H.I; Soetrilah Soetrilah; Masyhuri Masyhuri; Robet Asnawi; Retno S Wulandari (Politeknik Negeri Lampung, 2011)
This research aims to: (1) analyze the role of farmer cooperation/Koptan and KUD in increasing member income, (2) analyze the role of farmer cooperation/Koptan and KUD in improving the member welfare. The research is done by using descriptive method. The research location is determined in three districts of largest food production which have the most number of farmer cooperation/Koptan and KUD in Lampung Province. They are located in Central Lampung, South Lampung, and East Lampung. Each district is taken two farmer cooperations and two KUD purposively. Sample of farmers member from each farmer cooperation/Koptan and KUD is determined by five people. For comparison, the sample of non-member farmers in the farmer cooperation/Koptan or KUD region is also five people. Therefore all of the samples are 60 members of farmer cooperation /KUD and 60 non-members of Koptan/KUD. farmer cooperation and KUD role in increasing member income is analyzed by calculating the contribution of economic benefits on household income. farmer cooperation/Koptan and KUD role in improving the member welfare is analyzed by the poverty line criteria according to BPS, followed by One Way Anova. Farmer cooperation/Koptan and KUD have a role in increasing the income of its members, although it is not so large. This is demonstrated by the contribution of net economic benefits of member income obtained by farmer cooperation/Koptan or KUD members. The welfare level of farmer cooperation/Koptan and KUD members is higher than the welfare level of non-members of farmer cooperation/Koptan and KUD. Koptan and KUD have a role in improving the welfare of its members. the role of farmer cooperation/Koptan is greater than KUD. Keywords: role, farmer cooperation/Koptan and KUD, member welfare